2020
DOI: 10.1016/j.jcot.2020.07.011
|View full text |Cite|
|
Sign up to set email alerts
|

Minimal invasive surgery techniques for patients with adolescent idiopathic and early onset scoliosis

Abstract: Objective: Provide an update on minimal invasive surgery (MIS) techniques for surgical management of pediatric spine. Methods: Minimal Invasive surgery for pediatric spine deformity has evolved significantly over the past decade. We include updated information about the surgical management of patients with adolescent idiopathic and Early Onset Scoliosis through MIS techniques. We take into consideration the implementation of this technique in Low-to-Middle Income Countries (LMICs). Results: Although MIS began … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
0
1
Order By: Relevance
“…Moreover, the results indicate that the volume of blood loss correlated with the duration of operation, both after OSC and MIS treatment or number of vertebrae fused after MIS, which roughly corresponds to the values of other studies. 18,19 Compared to previous data from other scientists with a similar initial group, MIS in our study showed higher operative blood loss, but better coronal curve correction results. As in our study, the operative blood loss was 218.3 ± 17.1 mL with a corrected angle of 76.1 ± 11.1 as compared to that published by other authors who had an operative blood loss of 138.75 ± 50.04 mL with corrected angle of 68.25% ± 6.1 %.…”
Section: Discussioncontrasting
confidence: 53%
“…Moreover, the results indicate that the volume of blood loss correlated with the duration of operation, both after OSC and MIS treatment or number of vertebrae fused after MIS, which roughly corresponds to the values of other studies. 18,19 Compared to previous data from other scientists with a similar initial group, MIS in our study showed higher operative blood loss, but better coronal curve correction results. As in our study, the operative blood loss was 218.3 ± 17.1 mL with a corrected angle of 76.1 ± 11.1 as compared to that published by other authors who had an operative blood loss of 138.75 ± 50.04 mL with corrected angle of 68.25% ± 6.1 %.…”
Section: Discussioncontrasting
confidence: 53%